Measures of Pregnancy Intention: Why Use Them and What Do They Tell Us? - Dorney, Edwina; Barrett, Geraldine; Hall, Jennifer; Black, Kirsten I. (Seminars in Reproductive Medicine, 2022)
Understanding pregnancy intention is an important public health measure that captures the ability of individuals to access information, resources, and services needed to plan the timing and spacing of pregnancies. Pregnancy intention is a complex construct impacted by social, emotional, financial, cultural, and contextual factors. In this review, we will examine the range of available tools for individuals and populations to evaluate pregnancy intention, the timing of the tools in relation to pregnancy, their interpretation, and use for policy and practice. Traditionally, pregnancy intention was only assessed in population health surveys; however, more sophisticated tools and measures have been developed. These tools can be used at several time points: before pregnancy, during pregnancy, or after the pregnancy has ended. It is important to appreciate the varied contexts globally for women and their partners when assessing pregnancy intention, and the ability of a given tool to capture this when used retrospectively or prospectively. These tools can inform targeted delivery of services for a person or couple before, during, and after pregnancy. This knowledge can inform strategies at an individual, community, and population level as an indicator of access to sexual and reproductive health information and knowledge and uptake of preconception health.
Keywords: pregnancy intention; pregnancy planning; unplanned pregnancy; preconception; psychometric measure; measurement